2011
DOI: 10.1212/wnl.0b013e31820ee1bb
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA haplogroups and mutations in children with acquired central demyelination

Abstract: Objective: We investigated mitochondrial DNA (mtDNA) variants in children with a first episode of acquired demyelinating syndromes (PD-ADS) of the CNS and their relationship to disease phenotype, including subsequent diagnosis of multiple sclerosis (MS).Methods: This exploratory analysis included the initial 213 children with PD-ADS in the prospective Canadian Pediatric Demyelinating Study and 166 matched healthy sibling controls from the Canadian Autism Genome Project. A total of 31 single nucleotide polymorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
7
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
2
7
0
1
Order By: Relevance
“…By sequencing a subset of study participants, the authors concluded that the association is due to m.13708G.A and not the other haplogroup J SNPs (including m.295C.T) linked to this variant. The m.13708G.A variant was also significantly associated with pediatric acquired demyelination syndrome (PD-ADS), 23 providing further evidence to suggest that m.13708G.A is the SNP underlying the haplogroup J associations with MS and PPMS identified in the current study.…”
supporting
confidence: 71%
“…By sequencing a subset of study participants, the authors concluded that the association is due to m.13708G.A and not the other haplogroup J SNPs (including m.295C.T) linked to this variant. The m.13708G.A variant was also significantly associated with pediatric acquired demyelination syndrome (PD-ADS), 23 providing further evidence to suggest that m.13708G.A is the SNP underlying the haplogroup J associations with MS and PPMS identified in the current study.…”
supporting
confidence: 71%
“…Previous studies have found haplogroup J and multi-haplogroup categories that include J to be associated with decreased prevalence of Parkinson’s disease (Van Der Walt et al, 2003), neuroretinal disorder in HIV patients (Hendrickson et al, 2010), and acquired demyelinating syndrome (Venkateswaran et al, 2011). Conversely, findings from other studies suggest that haplogroup J is a risk factor for or not associated with these and other neurologic disorders (Jones et al, 2007; Kalman et al, 1999; Mehta et al, 2009; Reynier et al, 1999; Ross et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The investigators assessed nuclear (DRB1*1501) 1 and mitochondrial (various) 2 genetic variants in pediatric patients who present with acquired demyelinating syndromes. Two articles from the Canadian Pediatric Demyelinating Disease Network in the current issue of Neurology ® consider the frequency of 2 different putative biomarkers.…”
mentioning
confidence: 99%
“…2 The study evaluated a similar cohort of pediatric patients with acquired demyelinating syndromes. 2 The study evaluated a similar cohort of pediatric patients with acquired demyelinating syndromes.…”
mentioning
confidence: 99%
See 1 more Smart Citation